Regionalberichte und -pläne für Indonesien - Dürr, Heiner (ERDKUNDE, 1977)
In the course of the 'seventies' the central government of the Republic of Indonesia has displayed a variety of activities in the field of regional reporting and planning in order to fulfil the aims of regional-political equalisation under the Second Five Year Plan (1974-5 - 1979-80). One result has been a comprehensive series of regional studies, available as grey literature in limited editions. The chief aim of this contribution is to document the present state of this reporting and planning activity and to discuss their usefulness as well as possible subsequent tasks. In doing so three areas of concern come into focus: (1) geographical science (regional geography of Indonesia and general theory of regional development in South East Asia and the Third World), (2) actual and future practice of regional development in Indonesia as well as, (3) the policy of assignments for Western suppliers of development aid.